Informative Augmented Reality Based Products and Groceries Scanner - Ab Rahman, Nurulnadhirah; Nan Mad Sahar (Evolution in Electrical and Electronic Engineering, 2021)
Augmented Reality (AR) are used in applications in retail to achieve the Industrial Revolution 4.0 and retailers can be penalised if they do not display and misplace the price of their products following by the Act of 723 as the shopper’s time will be wasted looking for the price with information about the products especially for the Myopic people to read the information. The mobile device Augmented Reality application were design and develop by using a combination of Unity software and Vuforia SDK engine that act as a product and groceries scanner for 15 products in 2 supermarket by displaying the prices and information of items in the android operating system. The augmented reality application will run by analyzing mobile device camera capturing the motion and display output from the verification and validation method. The AR camera’s performance of speed in capturing and recognizing the physical object in a split seconds and it will display the output information when it is in a distance range of 25 cm until 55 cm from the product. The development of the augmented reality application is to help myopic people while purchasing groceries and reduce the time for users when performing shopping activities and this has been approved by the myopic people as the AR application has been tested to 11 different users. In the future, the AR scanner application needs to be upgraded to the iOS operating system and added more output information functions for the users.